New Records of the Genus Jessopocoris Carvalho, 1981 (Hemiptera: Miridae: Bryocorinae), with Descriptions of Two New Species Found in China - Mu, Yi-Ran; Liu, Guo-Qing (Zootaxa, 2012)
Three species of Jessopocoris Carvalho are presented, and J. yunnananus and J. aterovittatus, both from China, are described here as new to science. A key to species of Jessopocoris is given. Photographs of the dorsal habitus and illustrations of the dorsal view of hemelytra and the male genitalia are provided. Descriptions and illustrations of the male genitalic characters of Jessopocoris are provided for the first time.